Collisional activation of protein complexes: picking up the pieces. - Benesch, J (2009)
Mass spectrometry is fast becoming a vital approach not only for the identification and quantification of proteins, but also for the study of the noncovalent assemblies they form. Approaches for ionizing, transmitting, and detecting protein complexes intact in the mass spectrometer are now well established. The challenge has therefore shifted to developing and applying mass spectrometry approaches to elucidate the structure of such species. A crucial aspect to this goal is inducing their disassembly in the gas phase to mine information as to their composition and organization. Here the consequences of collisionally activating protein complexes are illustrated through ion mobility mass spectrometry measurements and discussed in the context of the current literature. Although a consensus view of the mechanism of dissociation is starting to emerge, it is also clear that a number of aspects remain unresolved. These outstanding questions and frontier challenges must be addressed if gas-phase dissociative approaches are to reach their full potential in the study of protein assemblies.